2019
DOI: 10.4193/rhin19.296
|View full text |Cite
|
Sign up to set email alerts
|

Predictive significance of Charcot-Leyden Crystal mRNA levels in nasal brushing for nasal polyp recurrence

et al.

Abstract: Background: Tissue eosinophils have been shown to be associated with polyp recurrence in chronic rhinosinusitis with nasal polyps (CRSwNP). We addressed whether the mRNA levels of Charcot-Leyden Crystal (CLC) in nasal brushing samples, a molecule mainly released from activated eosinophils, could serve as an effective non-invasive biomarker to predict polyp recurrence.Methods: A total of 51 patients with CRSwNP completing the postoperative follow-up over a period of 12-18 months were enrolled. Baseline CLC mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…Recurrence was de ned as the presence of nasal polyps observed under nasal endoscopy, together with at least one symptom (nasal obstruction, rhinorrhea, headache/facial pain, reduction or loss of smell, sleep disturbance/fatigue) lasting at least 1 week, despite appropriate intranasal corticosteroid treatment. The postoperative follow-up period was 18 months for assessment of recurrence/non-recurrence of nasal polyps [1,21]. All patients were followedup after weeks 1, 2, 4, and 12, and then once every three months for up to 18 months by the same surgeon, who was blinded to all laboratory data [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence was de ned as the presence of nasal polyps observed under nasal endoscopy, together with at least one symptom (nasal obstruction, rhinorrhea, headache/facial pain, reduction or loss of smell, sleep disturbance/fatigue) lasting at least 1 week, despite appropriate intranasal corticosteroid treatment. The postoperative follow-up period was 18 months for assessment of recurrence/non-recurrence of nasal polyps [1,21]. All patients were followedup after weeks 1, 2, 4, and 12, and then once every three months for up to 18 months by the same surgeon, who was blinded to all laboratory data [21].…”
mentioning
confidence: 99%
“…The postoperative follow-up period was 18 months for assessment of recurrence/non-recurrence of nasal polyps [1,21]. All patients were followedup after weeks 1, 2, 4, and 12, and then once every three months for up to 18 months by the same surgeon, who was blinded to all laboratory data [21]. Nasal tissue samples were collected from the inferior turbinate of control subjects and the nasal polyps of CRSwNP patients during surgery.…”
mentioning
confidence: 99%
“…Persson et al [32] have reported that crystallized CLCs are key features of severe eosinophilic inflammatory airway diseases, including asthma and CRSwNP. In our recently published study, we have confirmed a promising predictive significance of mRNA level of CLC in polyp tissue for eosinophilic CRSwNP and in nasal brushing for polyp recurrence [33, 34]. In addition, our previous study reported CLC protein concentrations in nasal secretions were significantly elevated in patients with better response to oral glucocorticoids (GCs) and higher percentage of tissue eosinophilia [35].…”
Section: Introductionmentioning
confidence: 62%
“…Clinically, increased levels of CLC protein have been reported to be present in nasal secretions in AR [13, 14], sputum in asthma [12], and nasal lavage fluid in patients with the aspirin-sensitive respiratory disease [39]. More recently, we have demonstrated that CLC mRNA and protein might serve as a marker in the identification of eosinophilic CRSwNP [40] as well as a reliable and alternative method for the prediction of glucocorticoid response in CRSwNP patients [15] and nasal polyp recurrence [41].…”
Section: Discussionmentioning
confidence: 99%